Effect of Polyamorphism on the Morphology, Dissolution, and Stability of Olaparib - Gao, Lu; Dai, Xia-Lin; Li, Shun-Yu; Vasilev, Nikita A.; Perlovich, German L.; Lu, Tong-Bu; Chen, Jia-Mei (Crystal growth & design, 2024)
Olaparib (OLA) is an insoluble targeting antitumor drug for the treatment of ovarian cancer. Herein, polyamorphism of OLA was systematically studied aiming to improve its solubility and dissolution properties. Three amorphous forms of OLA were prepared by ball milling (form I), rotary evaporation (form II), and melting (form III) methods, and the effects of polyamorphism on the morphology, thermodynamic properties, dissolution and gelation phenomenon, and the stability of OLA were studied for the first time. The results indicate that morphology has an impact on the gelation process of amorphous forms and thereby affects the dissolution of the drug. Among them, form II shows the best solubility and dissolution rate due to its slightest gelation, as well as relatively good stability and tabletability, which exhibits good application prospects in the amorphous solid formulation development of OLA.